Catalytic ozonation of ethyl benzene using modified pumice with magnesium nitrate from polluted air. Issue 3 (4th May 2017) - Samarghandi, Mohammad Reza; Daraee, Zahra; Shekher Giri, Balendu; Asgari, Ghorban; Reza Rahmani, Ali; Poormohammadi, Ali
Abstract: This paper reports a novel technology developed for a Catalytic Ozonation Process (COP) to treat polluted air streams containing ethyl benzene. Raw pumice was modified with magnesium nitrate, and then used as a catalyst in the COP. The best removal efficiency of ethyl benzene for single ozonation and single modified pumice was 58–80%, respectively at 50 ppm of this pollutant, while the maximum removal efficiency of ethyl benzene was 90% for COP (6 L/min of flow rate of inlet air, 15 g of the adsorbent, and 50 ppm of ethyl benzene). The saturation and breaking point of the catalyst in low concentrations occurred after 12 h, which was later than single ozonation. According to the results obtained, pumice modified with magnesium can be used as a cost effective, efficient and suitable catalyst to treat polluted air containing volatile organic compounds in the oil refining industries.